A GIS tool for automatic calculation of glacier equilibrium-line altitudes. (September 2015) - Pellitero, Ramón; Rea, Brice R.; Spagnolo, Matteo; Bakke, Jostein; Hughes, Philip; Ivy-Ochs, Susan; Lukas, Sven; Ribolini, Adriano
Abstract: A toolbox for the automated calculation of glacier equilibrium-line altitudes (ELAs) using the Accumulation Area Ratio, Area-Altitude Balance Ratio, Area-Altitude and Kurowski methods is presented. These are the most commonly-used methods of ELA calculation in palaeo-glacier reconstructions. The toolbox has been coded in Python and runs in ArcGIS requiring only the reconstructed surface of the palaeo-glacier (a DEM) as input. Through fast and automatic calculation this toolbox simplifies the process of ELA determination and can successfully work both for a single glacier and for large datasets of multiple glaciers. Highlights: We describe Equilibrium Line Altitude calculation methods for palaeoglaciers. We examine suitability of each method for different glacier types. We present a toolbox for automatic ELA calculation on AAR and AABR methods. Toolbox is coded in Python and runs in ArcGIS. Toolbox use and operation are described.